How do managers form their expectations about working from home? Survey experiments on the perception of productivity - Daniel Erdsiek; Vincent Rost (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
The recent shift towards working from home (WFH) has far-reaching implications for social and economic outcomes. While firms are gatekeepers for the ongoing diffusion of flexible work arrangements, there is little evidence on how firms decide to offer WFH. We leverage two survey experiments among nearly 800 knowledge-intensive services firms in Germany to analyse whether managers' beliefs about the productivity effects of WFH affect their adoption decisions. Exploiting exogenous variation in managers' information set, we find that managers update their beliefs about the productivity effects of WFH when they receive information on workers' self-assessed WFH productivity. In addition, the information treatment significantly increases managers' willingness to adopt or intensify WFH policies. Combining our main survey experiment with two follow-up surveys, we find persistent information treatment effects on both managers' beliefs about WFH productivity and firms' expected WFH intensity after the Covid-19 pandemic. A complementary survey experiment confirms our results pointing to a causal relationship between managers' beliefs about WFH productivity and the adoption of WFH practices. These findings have implications for potential policy measures targeting firms' WFH adoption.
Keywords: D22; D23; L22; O33; M54; 330; working from home; survey experiment; information provision; firm-level; managers; expectations